2020
DOI: 10.1186/s12885-020-07560-3
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional and inflammatory measures predict survival of patients with stage IV colorectal cancer

Abstract: Background This study aimed to evaluate the prognostic impact of nutritional and inflammatory measures (controlling nutritional status (CONUT) score, prognostic nutritional index (PNI), and modified Glasgow prognostic score (mGPS)) on overall survival (OS) in patients with stage IV colorectal cancer (CRC). Methods Subjects were 996 patients with stage IV CRC who were referred to the National Cancer Center Hospital between 2001 and 20… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 46 publications
1
17
0
Order By: Relevance
“…Furthermore, cancer-related systemic inflammation induces catabolism of patients, which causes metastasis 5 , 6 . Some inflammatory indices—neutrophil/lymphocyte ratio, platelet/lymphocyte ratio, and the modified Glasgow prognostic score—and several nutritional indices—the prognostic nutritional index, controlling nutritional status score (CONUT), sarcopenia, and geriatric nutritional index (GNRI)—can predict postoperative complications and long-term outcomes of several cancers 7 9 . These scores are also useful for evaluating postoperative complications and prognosis of HCC 10 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, cancer-related systemic inflammation induces catabolism of patients, which causes metastasis 5 , 6 . Some inflammatory indices—neutrophil/lymphocyte ratio, platelet/lymphocyte ratio, and the modified Glasgow prognostic score—and several nutritional indices—the prognostic nutritional index, controlling nutritional status score (CONUT), sarcopenia, and geriatric nutritional index (GNRI)—can predict postoperative complications and long-term outcomes of several cancers 7 9 . These scores are also useful for evaluating postoperative complications and prognosis of HCC 10 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, for their derived indexes PNI and NLR, cut offs of 36.5 and 4.8 were respectively calculated, but, due to the small sample size, they need further validation on a larger and more selected population. PNI is an unexpensive and easy to calculate parameter, which reflects the nutrition and inflammatory status of patients [ 30 ], whose role as a prognostic index for OS in many oncological settings has been widely recognised [ 31 ], [ 32 ], [ 33 ]. In our study, a PNI under the identified cut off value (36.5) resulted the only independently correlated factor with a worse OS (HR 2.41), and similar results were reported in a recent large retrospective study conducted on PM patients [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Over the past decade, relevant research has validated the prognostic impact of the CONUT score for solid tumors (6)(7)(8)(9). More recently, many studies have explored the association between the CONUT score and prognosis for hematologic malignancies most of which concluded that the CONUT score was an independent prognostic factor in patients with hematologic malignancies.…”
Section: Introductionmentioning
confidence: 99%